Wind and bone [videorecording (DVD)] - Troy, Kevin; Tuthill, Michael; Kashmanian, Julie; Cody, Alex; Oswald, Christine (Gravitas Ventures, 2025)
Wind and Bone is a psychological horror that delves into the darkness of the human psyche and the primal fear of the unknown...a woman on the run joins a group of college students in rural WV, where they come face to face with the Wendigo.